The antibacterial activity of Lactobacillus sp. GMP1 and Weisella sp. GMP12 against some foodborne disease causing-bacteria: Aktivitas antibakteri Lactobacillus sp. GMP1 dan Weisella ap. GMP12 terhadap beberapa bakteri pembawa penyakit pada makanan - Muhammad Yaafi’ Al-Hammam; Muhammad Prima Putra; Achmad Hanif Mardinsyah; Geta Cahyati; Indun Dewi Puspita (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Lactic acid bacteria (LAB) have been reported to have inhibitory activity against foodborne causative bacteria, some of which are generally recognized as safe (GRAS). The aim of this study was to isolate halotolerant lactic acid bacteria (HLAB) from fermented fish products, namely pakasam and wadi, and to determine their potential to inhibit the growth of contaminant bacteria and biogenic amine-producing bacteria. Isolation of HLAB was performed using De Man, Rogosa, and Sharpe agar (MRSA) supplemented with 1% CaCO3 and 7% NaCl. Colonies that grew and showed clear zones continued to undergo halotolerant growth tests in MRS broth with several NaCl concentrations. Two selected isolates were identified as lactic acid bacteria: Lactobacillus sp. GMP1 and Weisella sp. GMP12. The isolation of antibacterial compounds targeting bacteriocin was carried out by fermentation in MRSB media at 37°C for 24 h, followed by separation of the supernatant and isolation of the antibacterial compounds by precipitation with ammonium sulfate and dialysis. Antibacterial activity tests showed that bacteriocins produced by Lactobacillus sp. GMP1 and Weisella sp. GMP12 is able to inhibit Staphylococcus aureus ATCC 6,538 with bacteriocin activity of 5,868.19 AU and 3,693.60 AU, respectively. Bacteriocins can also inhibit Salmonella spp.. 230C with bacteriocin activity respectively is 1,696.39 AU and 2,254.17 AU, respectively, whereas only Weisella sp. GMP12 inhibits Klebsiella sp. CK2 with bacteriocin activity is 3,165.51 AU. These results indicate that Lactobacillus sp. GMP1 and Weisella sp. GMP12 has the potential to be used as a starter culture in fermented products.